Transformation of 2D group-III selenides to ultra-thin nitrides: enabling epitaxy on amorphous substrates. (28th September 2018) - Briggs, Natalie; Preciado, Maria Isolina; Lu, Yanfu; Wang, Ke; Leach, Jacob; Li, Xufan; Xiao, Kai; Subramanian, Shruti; Wang, Baoming; Haque, Aman; Sinnott, Susan; Robinson, Joshua A
Abstract: The experimental realization of two-dimensional (2D) gallium nitride (GaN) has enabled the exploration of 2D nitride materials beyond boron nitride. Here we demonstrate one possible pathway to realizing ultra-thin nitride layers through a two-step process involving the synthesis of naturally layered, group-III chalcogenides (GIIIC) and subsequent annealing in ammonia (ammonolysis) that leads to an atomic-exchange of the chalcogen and nitrogen species in the 2D-GIIICs. The effect of nitridation differs for gallium and indium selenide, where gallium selenide undergoes structural changes and eventual formation of ultra-thin GaN, while indium selenide layers are primarily etched rather than transformed by nitridation. Further investigation of the resulting GaN films indicates that ultra-thin GaN layers grown on silicon dioxide act as effective 'seed layers' for the growth of 3D GaN on amorphous substrates.